2019
DOI: 10.1097/md.0000000000017854
|View full text |Cite
|
Sign up to set email alerts
|

Impact of WNT1-inducible signaling pathway protein-1 (WISP-1) genetic polymorphisms and clinical aspects of breast cancer

Abstract: Breast cancer is the most common diagnosed malignancy in women. This study genotyped blood samples from 236 Han Chinese women with breast cancer and 128 healthy controls for single nucleotide polymorphisms (SNPs) rs2977537, rs2929970, rs2929973, rs2977530, and rs62514004, to determine whether these WNT1-inducible signaling pathway protein 1 (WISP-1) genetic polymorphisms increase the risk of developing breast cancer. Compared with wild-type (AA) carriers, those carrying the WISP1 rs62514004 AG or AG + GG genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…WISP1 polymorphisms have been identi ed in various cancers, including breast cancer [13], urothelial cell carcinoma [14], hepatocellular carcinoma [15], oral squamous cell carcinoma [16], lung cancer [17], uterine cervical cancer [18], but data are scant as to the involvement of WISP1 polymorphisms in gastric cancer. As far as we are aware, our study is the rst to investigate the distributions of the rs2929973, rs7843546 and rs10956697 SNPs and their associations with the development gastric cancer in Guangxi Chinese population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…WISP1 polymorphisms have been identi ed in various cancers, including breast cancer [13], urothelial cell carcinoma [14], hepatocellular carcinoma [15], oral squamous cell carcinoma [16], lung cancer [17], uterine cervical cancer [18], but data are scant as to the involvement of WISP1 polymorphisms in gastric cancer. As far as we are aware, our study is the rst to investigate the distributions of the rs2929973, rs7843546 and rs10956697 SNPs and their associations with the development gastric cancer in Guangxi Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, SNPs were selected based on data from the International HapMap Project (http://hapmap.ncbi.nlm.nih.gov/), dbSNP database (http://www.ncbi.nlm.nih.gov/projects/SNP/) and the nding of previous studies reported the effect of WISP1 genetic polymorphisms on cancer susceptibility [14][15][16][17][18][19]21]. All SNPs had minor allele frequencies (MAF) of > 5% to prevent false negative results.…”
Section: Selection Of Wisp1 Polymorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of WISP-1 in tumorigenesis has been studied in many types of neoplasms, where it acts as an autocrine and paracrine modulator, increasing cell migration [ 10 ]. Furthermore, the WISP-1 gene’s polymorphisms were shown to impact the breast cancer susceptibility and the expression of oestrogen and progesterone receptors in the tumour [ 16 ].…”
Section: Wisp-1 Multiple Functionsmentioning
confidence: 99%
“…TSU has been shown to affect the gene expression of P53 [ 25 ] by altering its negative regulator, the MDM2 gene [ 26 ], which in turn causes MDM2 upregulation in the lungs of cancer patients who are smokers [ 27 ]. Recently, single-nucleotide polymorphisms (SNPs) have also been linked to various diseases, including celiac disease [ 28 ], rheumatoid arthritis [ 29 ], bipolar disorder [ 30 ], and asthma [ 31 , 32 ], as well as lung [ 33 ], gastric [ 34 ], ovarian [ 35 ], and breast cancers [ 36 ]. Other studies have also demonstrated that TSU causes SNPs that affect gene expression in various locations in the genome [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%